The Growth And Production Of Soybean Plant (Glycine Max (L.) Merril) With Giving The Janjang Dust Of Oil Palm - Yunita Fitri; Armaini '; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Soybean has the high social economic velue and its part more strategic in the human life. The request of the seed and the production of soybean to be increasing along with the growth of society and the concumption per capita and also the increasing of the food nutrition of society condition. One of the effort to increase the productivity of soybean plant can using the manures. By giving Janjang dust of oil palm as the manure can increase the calium stock in the ground/land and then it can increase the calium absorbtion by plant. The act of cultivation/agriculture rubbish like the Janjang dust of the oil plam as manure can increase the production cost and also the plant management goodly and its cost is cheaper than KCl manure or the others calium manures. The purpose of this research to know the effect of the giving of Janjang dust of oil palm and to determine the good dose toward the growth and the production of the soybean plant. This research is done in the technician unit experiment of cultivation/agriculture faculty of Riau University. This research is started from November 2009 until February 2010. This research is done by using the complete random design (RAL) that consist of six treatments and four test, so it is gotten twenty four experiments. Every the Janjang dust treatment that given are A0= without janjang dust of oil palm, A1= 0,08 gram per plant (32 kg/ha), A2= 0,16 gram per plant (64 kg/ha), A3= 0,24 gram per plant (96 kg/ha), A4= 0,32 gram per plant (128 kg/ha), and A5= 0,4 gram per plant (160 kg/ha). The measured parameter is the high of plant (cm), the number of the effective leguminusae (fruit), the age of plant begin to flower (HST), the age of harvest (HST), the number of primary branch (fruit), the percentage of polong bernas (%), the weight of 100 dry seed (gram) and the weight of the dry seed (gram). The result of this research shown that the Janjang dust of oil palm treatment with dose 0,4 gram per plant (160 kg/ha) give the good effect for plant (cm), the number of the effevtive leguminusae (plant), the age of harvest (HST), the number of primary branch (fruit), the percentage of polong (%), the weight 100 dry seed and the weight of dry seed per, if seen by the growth and the production sides.   Keyword: Soybean Plant, Oil Palm,